THE INFLUENCE OF EDUCATIONAL LEVEL, WORK EXPERIENCE AND COMPREHENSION OF ACCOUNTING INFORMATION SYSTEM ON FINANCIAL REPORT QUALITY - Adiyanto, Fajar; Chomsatu Samrotun, Yuli; Wijayanti, Anita (eBA Journal: Journal Economics, Bussines and Accounting, 2018)
This study is conducted to: 1) test and analyze the influence of educational level on financial report quality; 2) test and analyze the influence of work experience on financial report quality; 3) test and analyze the influence of accounting information system on financial report quality. This type of research i.e. research with quantitative data sources in this study is the primary data. Population in this study is all employees employed in district financial department in Surakarta with the sample amounted of 30 employees, where all population was taken as sample. The technique in this study use the question form. The data analysis in a linear regression multiple series program spss for windows version 17.0. From data analysis known that the variabel work experience (H2) and accounting information system comprehension (H3) have influence on financial report quality, and the educational level (H1) variable has no influence on financial report quality, with in the regression coefficient values show that showed a negative value i.e. t count-0.985 and significant value of 0.334